Remote device monitoring shows long-term survival benefit in a propensity matched study of ICD patients. (19th May 2022) - Kolk, MZH; Tjong, FVY; Knops, RE
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Remote monitoring (RM) for implantable cardioverter defibrillators (ICDs) enables early detection of clinical events and reduces inappropriate shocks. However, although RM has been associated with improved clinical outcomes at short to medium-term follow-up, data on long-term survival benefit of RM is currently lacking. Purpose: To investigate long-term survival of patients using RM and compare this to a propensity score matched non-RM group. Methods: This is a retrospective, observational single-center analysis of patients ≥18 years old implanted with an ICD (single- and dual chamber, biventricular or subcutaneous ICDs) between 1995 and 2021. Data was extracted from the electronic health records. Patients were included in the RM group only if they were started on RM at some point during follow-up. To adjust for differences in baseline characteristics between RM and non-RM patients, propensity score matching was performed in a 1:1 fashion (caliper 0.20) using greedy matching. Estimation of the propensity score was done using logistic regression with RM as the outcome variable, adjusting for 17 covariates (age, gender, year of device implant, type of device, clinical variables and medication at baseline). Time-to-event analysis was performed using Kaplan Meier survival analysis, with significance indicated using a log rank P value. Hazard ratios and 95% confidence intervals (CI) were calculated using a Cox proportional-hazards model. Results: A total of 3199 ICD patients were included in this analysis. After propensity score matching for the probability of RM use, 1160 RM patients and 1160 non-RM patients with similar baseline characteristics were selected (mean age 59.1 ±14.8 years, 72.8% male). During a mean follow-up duration of 8.1 ±5.2 years, 363 (31.3%) patients died in the non-RM group and 111 (9.6%) patients died in the RM group (log rank p<0.001, Figure 1). The hazard ratio of RM for mortality was 0.261 (95 CI% 0.211 – 0.323, p=0.001). Conclusion: Long-term retrospective analysis indicates a significant survival benefit in ICD patients using RM.